Effect of crude propolis on the performance and feed digestibility of new zealand white rabbits - Piza, Paola Cristina de; Moreira, Bruna Leonel; Silva, Nhayandra Chistina Dias; Sodré, Pedro Ivo; Fonseca, Leonardo da Silva; Leite, Rafael Fernandes (Acta Scientiarum. Animal Sciences, 2021)
The objective of this study was to evaluate the performance and digestibility of diets containing different levels of crude propolis for growing rabbits. Forty-eight New Zealand White rabbits, 43 days old, of both genders, were used, distributed in a completely randomized design. There were four diets with different inclusion levels of crude propolis (0.0; 0.5; 1.0 and 1.5%). There was no statistical difference for performance regarding the inclusion levels of crude propolis (p = 0.85), as well as for the variables dry matter consumption, neutral detergent fiber and acid detergent fiber (p ≥ 0.07). Crude protein consumption showed a statistical difference in relation to gender (p = 0.04): males showed higher consumption. However, final weight, total weight gain, daily weight gain and feed efficiency were not influenced by the addition of crude propolis (p ≥ 0.37). Dry matter digestibility, crude protein, neutral detergent fiber and acid detergent fiber were not influenced by the inclusion levels of crude propolis in the diets (p ≥ 0.12). This study indicates that the inclusion of raw propolis up to 1.5% in the diets does not affect the performance parameters of rabbits.